IMPROVING MARKETING STRATEGIES IN TEXTILE INDUSTRIAL ENTERPRISES - Abdullazizova Khushnoza Nayabovna (Ecominds Press, 2025)
This article provides a classification of modern marketing conceptual methods that form the theoretical and methodological basis for the development of marketing strategies in the textile industry, the role of the textile industry in the country's economy and proposals for its development, as well as an eight-step sequence of marketing strategies network potential and existing problems have been studied, a process model for developing marketing strategies in the textile industry has been developed.
Keywords: Textile industry, marketing strategies, main strategic directions, sequence of marketing strategy implementation, cost-effectiveness, modern approaches.